Tata Laksana Refluks Gastroesofageal pada Anak: Tinjauan Pustaka - Agus Indra Yudhistira Diva Putra; Luh Putu Winansari Ratih; Veronica Lily Limantara; Anira Rema Aurelya; Komang Sutama Arta; Erick Kusuma Tandiono (PT Kalbe Farma Tbk., 2025)
Gastroesophageal reflux is common in adult population but mostly underdiagnosed in pediatric population. Diagnosis of gastroesophageal reflux in children is difficult and may masquerade as other gastrointestinal disease. This review discusses the management of gastroesophageal reflux in children especially in primary health care center to facilitate initial treatment and referral as needed.